Pengaruh struktur modal terhadap Return On Asset - Firdaus, Evan; Nurpadi, Dadi; Pratama, Intan Fajar (ARKA INSTITUTE, 2023)
The purpose of this study is to determine the capital structure factor on return on assets. The research method used in this study is the Survey Method with a Descriptive Analysis research approach and associative quantitative research form. The results of this study are that partially Capital Structure has a positive effect on Return On Assets (ROA). The level of closeness between Capital Structure and Return On Assets (ROA) based on Guilford's rule is close. Furthermore, the results of the coefficient of determination of the capital structure variable are that the capital structure variable affects ROA and the rest is influenced by other factors not examined in this study such as cash turnover, inventory turnover and debt turnover. It can be concluded that there is a positive relationship between Capital Structure and Return On Assets (ROA).